Age at natural menopause and factors affecting its onset: A cross-sectional study among postmenopausal females in District Dehradun - Singh, Pragya; Vyas, Shaili; Vallabh, Vidisha; Nautiyal, Ruchira; Srivastava, Abhay (Indian Journal of Community Health, 2022)
Background: Menopause has become a popular topic of study as life expectancy rises around the world. The average age at menopause in both developed and developing countries ranges from 45 to 53 years. Factors influencing the extent of ovarian follicle reserve dwindling, such as sociodemographic, menstrual, reproductive, and dietary factors. Aim and Objective: The present study aimed to determine the mean age of menopause and to find out the various factors affecting menopause onset. Methods: A community based cross-sectional study conducted in rural and urban areas of District Dehradun for a period of 1 year starting 1st August 2020 to 31st July 2021. Data were collected using multistage stratified random sampling from 211 cases of natural menopause. Chi-square was applied as statistical test of significance and p < 0.05 was considered statistically significant. Results: According to current study, average age menopausal age is 46 years. Variables like sociodemographic characteristics, lifestyle habits, reproductive and menstrual factors were found to have a significant relationship with onset of menopause. Conclusion: Menopause, whether it occurs early or late in life, several factors are responsible for deciding its onset. As a result, it is critical to identify the factors influencing the onset of menopause.